Nutritional rehabilitation after acute illness among older patients: A systematic review and meta-analysis. Issue 3 (March 2023) - Szklarzewska, Sylwia; Mottale, Raphael; Engelman, Edgard; De Breucker, Sandra; Preiser, Jean-Charles
Summary: Background & aims: Acute illness can lead to disability and reduced quality of life in older patients. The aim of this systematic review was to evaluate the effect of nutritional rehabilitation provided during and after hospitalisation for an acute event on functional status, muscle mass, discharge destination and quality of life of older patients. Methods: The protocol for this systematic review was registered in PROSPERO (CRD42021264971). Articles were searched using Scopus, Medline, Google Scholar and Clinical.trials.gov . For studies included in the meta-analysis, Hedges'g standardized mean difference effect size was calculated and transformed in odds ratios. Results: We identified 7383 articles, of which 45 publications (41 trials, n = 8538 participants, mean age 80.35 ± 7.01 years.) were eligible for the systematic review. Patients were hospitalized for acute medical diseases (n = 6925) and fractures (n = 1063). The interventions included supplementation with a fixed amount of oral nutritional supplements (ONS, n = 17 trials), individualized diet plan (n = 3), combination of physical exercise with nutrition therapy (n = 14 trials), combination of anabolic agents with nutrition therapy (n = 5 trials). Overall nutritional rehabilitation improved functional status (Odds ratio 1.63 [1.15; 2.3], p = 0.003) and muscle mass (Odds ratio 2.61 [1.22; 5.5], p = 0.01), but not the quality of life or the discharge destination. Conclusion: Nutritional rehabilitation was found to improve functional status and muscle mass. There is a need for larger studies involving older hospitalized patients.